2001
DOI: 10.1007/s002340000515
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the vertebral artery: report of two cases and review of the literature

Abstract: Duplication of the vertebral artery is rare. We report two cases in which it was an incidental finding. In the first, duplication of the right vertebral artery was demonstrated by magnetic resonance angiography (MRA) and conventional angiography. The second patient had duplication of the right vertebral artery demonstrated by MRA. We discuss the origin of this abnormality, its radiological implications and its potential clinical significance are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…At the same time, many arterial branches develop and form transient anastomoses between these two main primitive trunks which are; trigeminal arteries, otic arteries, hypoglossal arteries, and proatlantal arteries. 6,7 The anterior cerebral arterial circulation (CAC) originates from the ICA, while the BLNA gives rise to the vertebrobasilar system. 5 Approximately this same period of time, the ICA bifurcates into cranial and caudal divisions which is an important stage in cerebral artery embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, many arterial branches develop and form transient anastomoses between these two main primitive trunks which are; trigeminal arteries, otic arteries, hypoglossal arteries, and proatlantal arteries. 6,7 The anterior cerebral arterial circulation (CAC) originates from the ICA, while the BLNA gives rise to the vertebrobasilar system. 5 Approximately this same period of time, the ICA bifurcates into cranial and caudal divisions which is an important stage in cerebral artery embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The MACC and ACoP should ordinaryily regress and failure to do so for whatever reason (s) can lead to numerous anatomical variants, such as an accessory ACA as a result of persistence in MACC, or a double ACoA due to incomplete regression of the ACoP. 6 In the other hand, some segments that should persist may also regress abnormally giving rise to aplasia or hypoplasia of the proximal ACA segment. The complexity of adaptation process between the cerebral vessels, on the one hand, and the morphology and metabolic needs of the brain, on the other hand may be attributed to the dynamism of regression or persistence of certain segments resulting to anatomical variations.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 cases of this type of artery have been reported in the English literature, including this case [5][6][7][8][9][10][11][12][13][14][15][16][17][18], but not including cases that were described vaguely in the 19th century [4]. A summary of the cases is as follows.…”
Section: Discussionmentioning
confidence: 99%
“…They mostly appear to be coincidental findings, knowing that they are often associated with significant cerebrovascular abnormalities such as symptomatic kinking, aneurysm, arterio-venous fistulae and arterio-venous malformations [5]. Whereas fenestration of the extra-or intra-cranial vertebral artery is identified in 0.23% to 1.95% of angiographic or autopsic studies, duplication is much rarer with 22 reported cases in literature to date [6,7].…”
Section: Discussionmentioning
confidence: 99%